Oesophagopleural fistula and empyema following fishbone migration / Siti Aisyah Aliyas ... [et al.] - Aliyas, Siti Aisyah; Tuan Habib, Syarifah Najihah; Abdullah, Khairudin; Mohamad, Irfan (Faculty of Medicine, 2024)
Fishbone is one of the most commonly ingested foreign body encountered. Patient may present with foreign body sensation, dysphagia, odynophagia and drooling of saliva with positive history of foreign body ingestion. Depending on the site of impaction, it can either be removed in clinic setting or it may need surgical intervention, while some of the cases require further radiological imaging in order to locate the fishbone. In rare circumstances, the symptoms persist or worsen, possibly due to complications that may arise during surgery or the degree of severity of fishbone impaction itself. Herein we reported a case of migrated fishbone complicated with neck abscess and lung empyema following its migration.